Molecular signaling mechanisms that mediate exercise training effects on insulin sensitivity - Masaru Nagasaki; Yoshiharu Shimomura; Yuzo Sato (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Studies on exercise-induced stimulation of glucose uptake into skeletal muscle have indicated that components of the insulin signal transduction system, such as insulin receptor, IRS-1, and PI 3-kinase, are not involved in the mechanism of glucose uptake elicited by an acute bout of exercise, suggesting that the underlying molecular mechanism, by which an acute bout of exercise increases glucose uptake, is distinct from that of insulin. Sedentarism, maturation and dietary factors such as high-fat feeding cause insulin resistance, which is a result of defective signal transduction. On the other hand, exercise training and calorie restriction improve and prevent insulin resistance. The exercise training effects represented by improved insulin action in vivo are chiefly attributed to changes in body composition factors such as increased muscle volume and decreased body fat, and changes in post-insulin receptor mechanisms.